Potensi Padina australis sebagai Marine Drug untuk Aterosklerosis - Sadvika, I Gusti Ayu Stiti; Wulansari, Ni Wayan Ari; Suryaningsih, Ni Putu Elsinthia; Mahendra, Agung Nova (Faculty of Medicine Universitas Sebelas Maret, 2022)
Atherosclerosis is characterized by endothelial dysfunction, altered lipid accumulation, inflammation, and foam cells deposition. Fucoxanthin and fucoidan that are contained in Padina australis are known to have potential anti-atherosclerotic effects. This review aims to see the activity and potential of Padina australis as an anti-atherosclerotic marine drug. This literature review article was obtained through a online-based scientific database using terms or phrases relevant to the topic. Fucoxanthin reduces ROS and inhibits production of NO, PGE2, TNF-α, IL-6, and IL-1β. Meanwhile, fucoidan can regulate the development of atherosclerosis by preventing SMC from forming foam cells, LOX-1 expression, and proinflammatory molecules significantly. A decrease in total cholesterol, triglycerides, LDL, and increased HDL-c also shown to be one of the effects of fucoidan in modulating lipid metabolism. Fucoxanthin can increase thermogenesis by increasing PRDM16, UCP-1, and UCP-3 in BAT and decreasing adipocyte size, leptin, and increasing adiponectin in WAT. Fucoidan can lower the cholesterol index, triglycerides, LDL, and increase the expression of PPARγ which can increase lipid metabolism and inhibit hyperlipidemia. In conclusion, Padina australis is potential anti-atherosclerosis agent due to its fucoxanthin and fucoidan exhibiting antioxidant, anti-inflammatory effects, and modulation of lipid metabolism.Keywords: Padina australis, fucoxanthin, fucoidan, atherosclerosis, marine drug